1995
DOI: 10.1073/pnas.92.8.3521
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of blood pressure by the type 1A angiotensin II receptor gene.

Abstract: The renin-angiotensin system plays a critical role in sodium and fluid homeostasis. Genetic or acquired alterations in the expression of components of this system are strongly implicated in The renin-angiotensin system (RAS) is one of the primary physiological regulators of sodium and fluid balance (1). The RAS regulates body-fluid homeostasis through several distinct mechanisms-including effects on hemodynamics and vascular tone, direct stimulation of sodium reabsorption by the kidney, and stimulation of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
480
4
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(508 citation statements)
references
References 36 publications
18
480
4
2
Order By: Relevance
“…Figure 2A shows that blood pressures were significantly reduced in F 1 (C57BL/6 × 129) Agtr1a -/-mice (89 ± 8 mmHg) compared with wild-type controls (112 ± 3 mmHg; P = 0.03). The magnitude of the blood pressure reduction in Agtr1a -/-animals was very similar to that observed in our previous experiments using tail cuff manometry (2). We also analyzed a series of 24-hour blood pressure recordings and found that the general nature of blood pressure fluctuations was similar in Agtr1a +/+ and Agtr1a -/-mice ( Figure 2B), which indicated that the absence of AT 1A receptors does not affect qualitative patterns of diurnal variation in blood pressure.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Figure 2A shows that blood pressures were significantly reduced in F 1 (C57BL/6 × 129) Agtr1a -/-mice (89 ± 8 mmHg) compared with wild-type controls (112 ± 3 mmHg; P = 0.03). The magnitude of the blood pressure reduction in Agtr1a -/-animals was very similar to that observed in our previous experiments using tail cuff manometry (2). We also analyzed a series of 24-hour blood pressure recordings and found that the general nature of blood pressure fluctuations was similar in Agtr1a +/+ and Agtr1a -/-mice ( Figure 2B), which indicated that the absence of AT 1A receptors does not affect qualitative patterns of diurnal variation in blood pressure.…”
Section: Resultssupporting
confidence: 72%
“…The critical role of this pathway in regulation of blood pressure is highlighted by the impressive efficacy of angiotensinconverting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs) in patients with hypertension and in mice lacking the AT 1A receptor, the major murine AT 1 receptor isoform. These animals have very low blood pressure and profound salt sensitivity (2,3). Control of sodium excretion by the kidney has been suggested to be the critical mechanism for blood pressure regulation by the RAS (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice lacking the expression of these genes show that the AT1A receptor is far more important in the control of blood pressure. Systolic blood pressure is markedly reduced in mice that have no AT1A receptors while no significant difference of blood pressure is observed between wild type control animals and mice lacking the AT1B receptor gene [32][33][34]. Rat AT1A, AT1B and human AT1 5'-flanking region sequences have been determined.…”
Section: Regulation Of At1 Receptor Gene Expressionmentioning
confidence: 99%
“…13,[42][43][44][45] Gene-targeting studies further pointed out that these effects are mainly mediated by AT 1a receptors. 46,47 Knock out (À/À) of the AT 1a receptor gene decreased baseline blood pressure 46,48 and abolished the pressor response to Ang II infusion, 46,49 whereas deletion of AT 1b genes did not alter baseline blood pressure, nor the pressor response to Ang II. 46,50 Ang II induced dose-dependent increases in blood pressure in AT 1a (À/À) mice pretreated with an ACE inhibitor, which were inhibited by AT 1 receptor blockade.…”
Section: Angiotensin II At 1 and At 2 Receptorsmentioning
confidence: 99%